The benefits and challenges of using AI at schools for teachers - Vokhmina, Alexandra; Ma, Linus (My University, 2025)
This study explores the benefits and challenges regarding the integration of artificial intelligence (AI) in teaching, focusing on how AI can support education while also addressing concerns posed by AI. Findings from the literature review reveal that AI contribute positively to student engagement and learning outcomes due to individualized educational experiences. However, major concerns arise including lack of training for teachers in effectively using AI, ethical problems, and possible bias in AI content. Many educators are not ready to integrate AI effectively due to existing misconceptions on AI and limited school support. Despite the growing presence of AI in modern education, the importance of real human emotional connections in classroom teaching should not be understated. This study suggests that AI tools should be implemented in teaching with careful consideration with regards to teacher training. Moreover, it is essential to create training courses among teachers, establish ethical guidelines and offer support to strengthen their AI literacy. The research contributes to a better understanding of effective and responsible AI integration into education and encourages thoughtful adoption among current and future teachers.
Keywords: AI, Education, In-service teachers, Pre-service teachers, Benefits, Challenges